2008
DOI: 10.1016/j.nano.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry influences cancer killing effect of TiO2 nanoparticles

Abstract: Photocatalyzed TiO 2 nanoparticles have been shown to eradicate cancer cells. However the required in situ introduction of UV light limits the use of such a therapy in patients. In the present study, the non-photocatalyic anti-cancer effect of surface functionalized TiO 2 was examined. Nanoparticles bearing -OH, -NH2, or -COOH surface groups, were tested for their effect on in vitro survival of several cancer and control cell lines. The cells tested included B16F10 melanoma, Lewis lung carcinoma (LLC), JHU pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(125 citation statements)
references
References 57 publications
(76 reference statements)
7
113
0
2
Order By: Relevance
“…[28][29][30] In addition to surface functionalization, other factors such as particle size, shape, surface charge, and surface functionality also affect the interactions between particles and cells. 31,32 In our study, iron oxide NP surface was modified with dextran as confirmed by FTIR analysis. Utilizing DIONPs, we observed that the size of NPs in culture media was greater than its primary size, which is most likely due to the formation of the protein corona on the NPs in the buffer medium.…”
Section: Discussionmentioning
confidence: 59%
“…[28][29][30] In addition to surface functionalization, other factors such as particle size, shape, surface charge, and surface functionality also affect the interactions between particles and cells. 31,32 In our study, iron oxide NP surface was modified with dextran as confirmed by FTIR analysis. Utilizing DIONPs, we observed that the size of NPs in culture media was greater than its primary size, which is most likely due to the formation of the protein corona on the NPs in the buffer medium.…”
Section: Discussionmentioning
confidence: 59%
“…68 Wu et al 93 have 94 It is known that surface functionality of nanomaterials directly affects cell viability and intracellular particle accumulation. 83,95 Both graphene and SWCNTs induce cytotoxic effects, which depend on their concentration and shape.…”
Section: Concentrations (µG/ml) Ros Generation (Fold Increase)mentioning
confidence: 99%
“…To date, most nanotoxicity research has been focused on individual nano-sized metal oxides. The potential toxicity of nanoparticles, including nickel oxide (NiO), titanium dioxide (TiO 2 ), carbon nanotubes, and fullerenes, has drawn significant attention [13][14][15][16]. For example, NiO particles have been shown to trigger reactive oxygen species (ROS) that cause DNA damage in lungs of rats [13].…”
Section: Introductionmentioning
confidence: 99%